2015
DOI: 10.1002/ccr3.313
|View full text |Cite
|
Sign up to set email alerts
|

Double deletion of a chromosome 21 inserted in a chromosome 22 in an azoospermic patient

Abstract: Key Clinical MessageWe report on a phenotypically normal 41-year-old azoospermic man with a 45 chromosomes karyotype including one normal chromosome 21, one normal chromosome 22, and a der(22)ins(22;21). Array CGH showed a 1.8 Mb terminal deletion of bands 21pter to 21q21.1 and a 341 kb terminal deletion on band 21q22.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Also, previous reports showed that individuals with 21q deletion can be infertile, presenting azoospermia or irregular menstrual cycles (Marquet et al ). The present patient has no history of other reproductive disorders or neoplasias until now, but she developed a severe polymenorrhea, which has lead to hysterectomy.…”
mentioning
confidence: 96%
“…Also, previous reports showed that individuals with 21q deletion can be infertile, presenting azoospermia or irregular menstrual cycles (Marquet et al ). The present patient has no history of other reproductive disorders or neoplasias until now, but she developed a severe polymenorrhea, which has lead to hysterectomy.…”
mentioning
confidence: 96%
“…Chromosomal abnormalities, including aneuploidies, deletions, microdeletions of the AZF region of the Y chromosome, duplications, small supernumerary marker chromosomes, translocations, insertions, and inversions, may be the underlying cause of the failure to complete meiosis45678910111213141516. Such chromosomal aberrations have been shown to affect meiotic synapsis and chromosome pairing17, resulting in both infertility and spontaneous abortions.…”
mentioning
confidence: 99%